2018
DOI: 10.1038/s41563-018-0144-z
|View full text |Cite
|
Sign up to set email alerts
|

Robust microscale superlubricity in graphite/hexagonal boron nitride layered heterojunctions

Abstract: Structural superlubricity is a fascinating tribological phenomenon, in which the lateral interactions between two incommensurate contacting surfaces are effectively cancelled resulting in ultralow sliding friction. Here we report the experimental realization of robust superlubricity in microscale monocrystalline heterojunctions, which constitutes an important step towards the macroscopic scale-up of superlubricity. The results for interfaces between graphite and hexagonal boron nitride clearly demonstrate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
306
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 370 publications
(324 citation statements)
references
References 47 publications
17
306
0
1
Order By: Relevance
“…For strains higher than 0.50% the ILSS fluctuates along low values in the range of ~40-50 KPa which indicates that the flake is practically sliding from that level of strain onwards 16 , as a result of the axial tensile force acting at the right edge of the flake. Another very interesting point, is that the maximum and minimum ILSS for the two-layer graphene is also in very good agreement with recent results for Bernal bi-layer graphene, shearing graphite mesas, and with a hBN/graphene heterojunction 18 . The measured ILSS in the range ~0.07-0.13 MPa, as well as the 40-50 kPa values recorded for the higher strain levels, are in the corresponding range of frictional stresses associated with superlubric behavior 16 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For strains higher than 0.50% the ILSS fluctuates along low values in the range of ~40-50 KPa which indicates that the flake is practically sliding from that level of strain onwards 16 , as a result of the axial tensile force acting at the right edge of the flake. Another very interesting point, is that the maximum and minimum ILSS for the two-layer graphene is also in very good agreement with recent results for Bernal bi-layer graphene, shearing graphite mesas, and with a hBN/graphene heterojunction 18 . The measured ILSS in the range ~0.07-0.13 MPa, as well as the 40-50 kPa values recorded for the higher strain levels, are in the corresponding range of frictional stresses associated with superlubric behavior 16 .…”
Section: Resultssupporting
confidence: 87%
“…Despite the stress concentration that might be present in such cases, the mismatch in the lattice constant between the two layers eliminates such effects. For example, as explained in the case of hBN/graphene interface with inherent lattice constant mismatch 18 , the possible presence of small friction anisotropy does not alter the overall system behaviour. Moreover, MD simulations on shearing a graphene layer on a strained graphene, show that the friction dramatically decreases with the increase in graphene size.…”
Section: Preparation and Testing Of Cvd Samplementioning
confidence: 96%
“…Lateral force, F l of microscale superlubricity in graphite is presented F1= 2γgL where γ g is the surface energy of the graphite basal plane, and L is the contact width. The calculated results using Equation is in good agreement with experimental results previously reported . The average number of MS is 54.4 on the contact areas, which was measured from the SEM images on 78 contact areas after sliding of macroscale superlubricity, as depicted in Figure S6a in the Supporting Information.…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, substantial progress has been recently done by Song et al toward the realization of robust structural lubricity for graphite and hexagonal boron‐nitride interfaces. They reported observations of robust structural lubricity in microscale monocrystalline heterojunctions and demonstrated that structural superlubricity persists even when the aligned contact sustains external loads under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%